Perceived Influence of Reformation on Juvenile Delinquents in Borstal Training Institution, Kaduna State, Nigeria - Saaka, Deborah Ahemen; Doka, Jerry; Salihu, Yunana Ulea (NIU Journal of Humanities; Vol 6 No 4 (2021): KIU Journal of Humanities, Vol. 6 No. 4, December 2021, 2022)
The research investigated the perceived influence of reformation on juvenile delinquents in borstal training institution, Kaduna. The research adopted a survey design, a total number of 73 participants were sampled and data was collected using a structured questionnaire. Chi-square, Pearson Correlation and Independent t-test were used to analyse the hypotheses. Hypothesis one revealed a non-significant association x 2 (3) = 5.588, p>0.05 between delinquents’ reformation and length of stay. Therefore, the hypothesis was rejected. Hypothesis two revealed a statistical negative significant relationship r (71) = - 0.298, p<0.05 between delinquents’ reformation and humane treatment. Hypothesis two was accepted and hypothesis three revealed a statistical non-significant difference t (71) = - 0.872, p>0.05 between academic and vocational training. The research rejected hypothesis three and accepted the null hypothesis. It is therefore concluded and recommended that government should provide modern techniques and equipment for both academic and vocational trainings delinquents receive in the institution. Keywords: Perceived Influence, Reformation, Juvenile Delinquents and Borstal Training Institution